Modelling and analyses of WSN-based pursuit-evasion strategies for multi-pursuers to multi-evaders. (3rd January 2011) - Guo, Li-Xin; Xie, Hua-Long; Zhao, Lei-Ping; Wang, Zhao-Wen
Wireless sensor networks have yielded a lot of new theoretical problems for the localisation, tracking and navigation control of mobile objects within a local area, especially, for investigations of pursuit-evasion games. For the efficiency of capture and evasion of pursuers and evaders in pursuit-evasion games, several novel pursuit-evasion policies are proposed in this study. The vector-ward evasion strategy may bring the evader breaking away from the puzzledom between two fires and reduce fluctuation of evasion routes. The intelligent collaboration pursuit strategy effectively exerts the collaboration efficiency of multiple pursuers and shortens the capture time. The estimated location errors caused by wireless sensor networks were also involved for the pursuers and evaders in the simulation of this study. The results show that every pursuit-evasion strategy is valid and robust. In the simulation of multiple pursuers to capture multiple evaders, the object assignment method and the corresponding pursuit policies are reliable and can capture all evaders in a limited area as quickly as possible.